Enhancing physical performance in male volleyball players with a caffeine-containing energy drink - Del Coso, J.; Perez-Lopez, A.; Abian-Vicen, J.; Salinero, J. J.; Lara, B.; Valades, D. (International Journal of Sports Physiology and Performance, 2014)
There are no scientific data about the effects of caffeine intake on volleyball performance. The aim of this study was to investigate the effect of a caffeine-containing energy drink to enhance physical performance in male volleyball players. A double-blind, placebo-controlled, randomized experimental design was used. In 2 different sessions separated by 1 wk, 15 college volleyball players ingested 3 mg of caffeine per kg of body mass in the form of an energy drink or the same drink without caffeine (placebo). After 60 min, participants performed volleyball-specific tests: standing spike test, maximal squat jump (SJ), maximal countermovement jump (CMJ), 15-s rebound jump test (15RJ), and agility T-test. Later, a simulated volleyball match was played and recorded. In comparison with the placebo drink, the ingestion of the caffeinated energy drink increased ball velocity in the spike test (73 ± 9 vs 75 ± 10 km/h, P < .05) and the mean jump height in SJ (31.1 ± 4.3 vs 32.7 ± 4.2 cm, P < .05), CMJ (35.9 ± 4.6 vs 37.7 ± 4.4 cm, P < .05), and 15RJ (29.0 ± 4.0 vs 30.5 ± 4.6 cm, P < .05). The time to complete the agility test was significantly reduced with the caffeinated energy drink (10.8 ± 0.7 vs 10.3 ± 0.4 s, P < .05). In addition, players performed successful volleyball actions more frequently (24.6% ± 14.3% vs 34.3% ± 16.5%, P < .05) with the ingestion of the caffeinated energy drink than with the placebo drink during the simulated game. A caffeine-containing energy drink, with a dose equivalent to 3 mg of caffeine per kg body mass, might be an effective ergogenic aid to improve physical performance and accuracy in male volleyball players.